REMOVAL OF SULFUR DIOXIDE FROM FLUE GAS USING ABSORBENT PREPARED BY WATER AND STEAM HYDRATION - Teong, Lee Keat; Mohamed, Abdul Rahman; Bhatia, Subhash (ASEAN Journal on Science and Technology for Development, 2003)
Active absorbent for flue gas desulfurization was prepared from coal fly ash, calcium oxide (CaO) and calcium sulfate (CaSO4 ) by hydro-thermal process; steam and water hydration. The absorbents were examined and compared for its micro-structural properties. The experiments were conducted based on Design of Experiments (DOE) according to 24 factorial design. The effect of various absorbent preparation variables such as hydration period (Factor A), ratio of CaO to fly ash (Factor B), amount of calcium sulfate used (Factor C) and drying temperature (Factor D) towards the BET surface area of the absorbent were studied. The BET surface area of the absorbent was in the range of 12.9-169.3 m2/g. Fisher’s test showed that there is a strong influence of factor A, B and D towards the absorbent surface area, while its dependence on factor C is negligible. Comparison between absorbents prepared from water and steam hydration showed that the BET surface area of absorbents prepared from water hydration gives a higher surface area, but at a lower rate. The optimum BET surface area for the prepared absorbent 169.3 m 2 /g, was obtained at the following absorbent preparation variables using water hydration; hydration period of 24 hours, ratio of CaO to fly ash of 1:2, CaSO4 amount of 3 g and drying temperature of 200°C.